A season of gifts - Peck, Richard, 1934- (Puffin Books, 2010)
Relates the surprising gifts bestowed on twelve-year-old Bob Barnhart and his family, who have recently moved to a small Illinois town in 1958, by their larger-than-life neighbor, Mrs. Dowdel.